Effect of Preparation Methods on Al2O3 Supported CuO-CeO2-ZrO2 Catalysts for CO Oxidation - Gaurav Rattan; Ram Prasad; Ramesh C. Katyal (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2012)
To examine the effect of preparation methods, four catalyst samples having same composition (CuCe5.17Zr3.83Ox/g-Al2O3 (15wt%) were prepared by four different methods for CO oxidation. The catalysts were prepared by co-impregnation, citric acid sol-gel, urea nitrate combustion and urea gelation co-precipitation methods, and characterized by BET, XRD, TGA/DSC and SEM. The The air oxidation of CO was carried out in a tubular fixed bed reactor under the following operating conditions: catalyst weight - 100 mg, temperature - ambient to 250 oC, pressure - atmospheric, 2.5% CO in air, total feed rate - 60 ml/min. It was observed that the catalytic activity greatly influenced by the preparation methods. The highest activity of the catalyst prepared by the sol gel method appeared to be associated with its largest BET surface area. All the four catalysts were active for CO oxidation and did not show deactivation of catalytic activity for 50 hours of continuous runs. The ranking order of the preparation methods of the catalyst is as follows: sol-gel > co-impregnation > urea gelation > urea nitrate combustion. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)